JWST Discovery of Warm Dust in the Circumgalactic Medium of the Makani Galaxy - Sylvain Veilleux; Steven D. Shockley; Marcio Meléndez; David S. N. Rupke; Alison L. Coil; Aleksandar M. Diamond-Stanic; James E. Geach; Ryan C. Hickox; John Moustakas; Gregory H. Rudnick; Paul H. Sell; Christy A. Tremonti; et al. (The Astrophysical Journal)
We report the detection of near- and mid-infrared emission from polycyclic aromatic hydrocarbons (PAHs) out to ∼35 kpc in the Makani Galaxy, a compact massive galaxy with a record-breaking 100 kpc scale starburst-driven wind at redshift z = 0.459. The NIRCam and MIRI observations with JWST take advantage of a coincidental match between the PAH spectral features at 3.3, 7.7, and (11.3 + 12.2) μ m in Makani and the bandpasses of the MIRI and NIRCam filters. The warm dust is not only detected in the cool-gas tracers of the galactic wind associated with the more recent (7 Myr) starburst episode, but also in the outer warm ionized gas wind produced by the older (0.4 Gyr) episode. The presence of PAHs in the outer wind indicates that the PAHs have survived the long ( R / v ∼ 10 ^8 yr) journey to the halo despite the harsh environment of the galactic wind. The measured F1800W/F1130W flux ratios in the unresolved nucleus, inner halo ( R = 10–20 kpc), and outer halo ( R = 20–35 kpc), tracers of the PAH (11.3 + 12.2)/7.7 ratios, indicate decreasing starlight intensity incident on the PAHs, decreasing PAH sizes, and increasing PAH ionization fractions with increasing distance from the nucleus. These data provide the strongest evidence to date that the ejected dust of galactic winds survives the long journey to the circumgalactic medium, but is eroded along the way.